Bringing biomechanics to ballet: a feasibility study using wearable technology during grand allegro - Swords, T.; McClelland, J.; Middleton, K.; Tessarin, B.; Bryce, S.; Mayes, S.; Rio, E. (Sports Biomechanics, 2024)
Quantifying impact accelerations during ballet class may assist load management. The largest impact accelerations occur during the sequence of large (single or double-leg) jumps (grand allegro) but are potentially the most challenging class component for utilising wearable technology, and feasibility is unknown. This pilot study utilised wearable technology during class to (1) explore feasibility and acceptability, (2) quantify impact accelerations during the entire sequence of jumps during grand allegro and (3) compare impact accelerations between limbs (preferred and non-preferred landing limb). Twelve pre-professional ballet dancers (18 ± 0.71 years old, eight females) wore inertial measurement units on each leg during class and reported acceptability. Total impact accelerations and percentage differences between limb loading during allegro were calculated. Most dancers (n = 11) reported wearable technology was feasible/acceptable during class. There were no significant differences between impact accelerations of preferred and non-preferred limb (p = 0.72) nor between limb comparison (p = 0.18). Most dancers were symmetrical (90% to 110%) in limb loading (N = 8). Wearable technology was considered acceptable during ballet class, opening future exploration of the whole class, different classes and rehearsals, as well as potential use for returning dancers back from injury.